Limited uptake of ulcerative colitis "treat‐to‐target" recommendations in real‐world practice. Issue 3 (22nd February 2018) - Bryant, Robert V; Costello, Samuel P; Schoeman, Scott; Sathananthan, Dharshan; Knight, Emma; Lau, Su‐Yin; Schoeman, Mark N; Mountifield, Reme; Tee, Derrick; Travis, Simon P L; Andrews, Jane M
Abstract: Background and Aims: A "treat‐to‐target" approach has been proposed for ulcerative colitis (UC), with a target of combined clinical and endoscopic remission. The aim of the study was to evaluate the extent to which proposed targets are achieved in real‐world care, along with clinician perceptions and potential challenges. Methods: A multicentre, retrospective, cross‐sectional review of patients with UC attending outpatient services in South Australia was conducted. Clinical and objective assessment of disease activity (endoscopy, histology, and/or biomarkers) was recorded. A survey evaluated gastroenterologists' perceptions of treat to target in UC. Statistical analysis included logistic regression and Fisher's exact tests. Results: Of 246 patients with UC, 61% were in clinical remission (normal bowel habit and no rectal bleeding), 35% in clinical and endoscopic remission (Mayo endoscopic sub‐score ≤ 1), and 16% in concordant clinical, endoscopic, and histological (Truelove and Richards' Index) remission. Rather than disease ‐related factors (extent/activity), clinician ‐related factors dominated outcome. Hospital location and the choice of therapy predicted combined clinical and endoscopic remission (OR 3.6, 95% CI 1.6–8.7, P  < 0.001; OR 3.3, 95% CI 1.1–12.5, P  = 0.04, respectively). Clinicians used C‐reactive protein more often than endoscopy as a biomarker for disease activity (75% vs 47%, P  < 0.001). In the survey, 45/61 gastroenterologists responded, with significant disparity between clinician estimates of targets achieved in practice and real‐world data ( P  < 0.001 for clinical and endoscopic remission). Conclusions: Most patients with UC do not achieve composite clinical and endoscopic remission in "real‐world" practice. Clinician uptake of proposed treat‐to‐target guidelines is a challenge to their implementation.